A new non-degradative method to purify glycogen. (20th August 2016) - Tan, Xinle; Sullivan, Mitchell A.; Gao, Fei; Li, Shihan; Schulz, Benjamin L.; Gilbert, Robert G.
Highlights: Glycogen: a complex glucose polymer also containing small amount of protein. Need to isolate undegraded liver glycogen from the many proteins in the liver. Size exclusion chromatography separates proteins and glycogen by size. New technique tested using proteomics. Succeeds in separating glycogen from huge number of extraneous proteins. Abstract: Liver glycogen, a complex branched glucose polymer containing a small amount of protein, is important for maintaining glucose homeostasis (blood-sugar control) in humans. It has recently been found that glycogen molecular structure is impaired in diabetes. Isolating the carbohydrate polymer and any intrinsically-attached protein(s) is an essential prerequisite for studying this structural impairment. This requires an effective, non-degradative and efficient purification method to exclude the many other proteins present in liver. Proteins and glycogen have different ranges of molecular sizes. Despite the plethora of proteins that might still be present in significant abundance after other isolation techniques, SEC (size exclusion chromatography, also known as GPC), which separates by molecular size, should separate those extraneous to glycogen from glycogen with any intrinsically associated protein(s). A novel purification method is developed for this, based on preparative SEC following sucrose gradient centrifugation. Proteomics is used to show that the new method compares favourably with current methods in the literature.